Thermoregulation and Soil Moisture Management in Strawberry Cultivation Mulched with Sheep Wool - Jan Broda; Andrzej Gawłowski; Monika Rom; Tomasz Kukulski; Katarzyna Kobiela-Mendrek (Applied Sciences)
The application of wool as mulch in strawberry cultivation was analysed to find a solution for the rational use of wool from mountain sheep. In the plantation, the experimental plots mulched with wool, straw, and bark were appointed. The plots were monitored during the experiment, while the soil temperature and moisture content were measured. The data collected in two-hour intervals were analysed, taking into account air temperature and falls registered in the local meteorological station. Additionally, the progress of mulch biodegradation was tracked. The changes in the wool morphology that occurred by biodegradation were observed during microscopic examinations using the Scanning Electron Microscope (SEM). It was stated that wool mulch plays an essential role in thermoregulation of the soil surface, prevents the overheating of the soil during the summer heat, and protects soil against excessive cooling during cold nights. The wool mulch minimizes the fluctuations between the soil’s day and night temperature. The fluctuations do not exceed 2–3 degrees on hot summer days, which are five times smaller than for the control plot. The wool retains large amounts of rainwater several times its weight. The water is then slowly released, providing the growing plants with a moist environment during a longer rainless period. Moreover, wool is difficult to biodegrade and maintains its properties for a long time, lasting longer than one vegetation season. Compared to straw and bark, the temperature fluctuations recorded for wool are two times smaller, and its effectiveness in water management is considerably better. The beneficial impact of the wool mulch ensuring favourable conditions for strawberry growth was explained by the specific wool structure and its unique properties.